The International and Political Journal: National and International Efforts to Combat Terrorism (ISIS as a model) - Hasan, Lecturer Dr. Hanan Faleh (The International and Political Journal, 2024)
This research, “National and International Efforts to Combat Terrorism and Extremism in Iraq - ISIS as a Model”, addressed the nature of terrorism, and highlighted the national efforts made to combat ISIS by following military, educational, social, and religious measures. In addition, it deals with the international efforts made to establish an international coalition and to issue resolutions by the Security Council in order to combat terrorism and terrorist financing. Moreover, it discussed the participation of international organizations in that coalition to confront extremist groups in Iraq. National and international efforts have resulted in eliminating terrorist groups and liberating the territories they seized.